Violência na infância, trauma e vulnerabilidade à psicopatologia - Schestatsky, Sidnei Samuel (Revista de Psicanálise da SPPA, 2014)
O artigo introduz a questão da violência contra crianças e adolescentes em termos globais e relembra seu caráter epidêmico atual. Examina a entrada do tema violência na psicanálise, a partir dos conceitos do trauma real e trauma psíquico, comentando sobre a atualidade e permanência do trauma como um problema clínico e metapsicológico incontornável a ser enfrentado pela psicanálise. Faz um breve histórico da evolução dos quadros traumáticos na psiquiatria e na psicanálise até a introdução do Transtorno de Estresse Pós-Traumático (TEPT) no DSM-III. Discutem-se as vulnerabilidades decorrentes do impacto da violência crônica em crianças e se descrevem evidências relevantes sobre a associação entre violência-trauma-vulnerabilidade-psicopatologia na idade adulta, especialmente no Transtorno de Personalidade Borderline. O artigo se encerra com considerações sobre alguns modelos psicanalíticos do trauma, priorizando diversas contribuições fundamentais de Ferenczi para a construção do entendimento contemporâneo do trauma psíquico, seus principais mecanismos e suas sequelas. Violence in childhood, trauma and vulnerability to psychopathology The article introduces the subject of violence against children and adolescents in global terms and recalls its current epidemic feature. Examines the entrance of the topic violence in psychoanalysis, taking as a starting point the concepts of true trauma and psychic trauma, commenting on the up-to-dateness and permanence of trauma as an unavoidable clinical and metapsychological problem to be faced by the psychoanalysis. It provides a brief background on the evolution of traumatic disorders in psychiatry and in psychoanalysis until the introduction of Post Traumatic Stress Disorder (PTSD) in the DSM-III. The article discusses the vulnerabilities that arise from the impact of chronic violence in children and describes relevant evidences on the association between violence-trauma-vulnerability-psychopathology in the adult, especially for Borderline Personality Disorder. It finishes with considerations on some psychoanalytical models of trauma, giving priorities to many contributions by Ferenczi which are decisive for the construction of contemporary understanding of psychic trauma, its main mechanisms, and sequelae.